The Causes of Student’s Reluctance to Ask Question’s When Attending Lectures - Hanif Naufal Salim (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The objective of the research was to find out the causes and the dominant cause of students' reluctance to ask questions when attending lectures of English Study Program of Muhammadiyah University of Bengkulu. The design of this research was descriptive method. The instrument of the research was questionnaire. The questionnaire was based on Hamouda (2012) about factor causes of the students reluctance in classroom. The result showed that there are four factors of causes the students reluctant, they are: lack of motivation, anxiety, fear making mistake and lack of confidence, but in this research only found three factors they are anxiety, fear making mistake and lack of confidence. The dominant factor of students reluctant to ask question they are: anxiety and fear making mistake. It is suggested the students to diminish the students reluctant to ask question when attending lectures the students have to more practice to speak English, always try to ask question, prepare that everything before come to the class and be confidence about themselves. Key words: Learning, Asking Question, Students Reluctan